Підвищення ефективності твердопаливних котлів - Стручаєв, Микола Іванович; Стручаев, Николай Иванович; Struchaiev, Mykola (ТДАТУ, 2019)
UK: В роботі запропоновано один із варіантів підвищення ефективності використання енергії палива при роботі твердопаливних котлів шляхом зниження втрат теплової енергії зменшенням температури димових газів на виході з топки за рахунок встановлення додаткових поверхонь нагріву, а саме – економайзера. Розглянуто алгоритм розрахунку водяного економайзера для твердопаливних котлів з метою підвищення його енергоефективності. Запропоновано схему розташування економайзера малої потужності на базі вітчизняних агрегатів. RU: В работе предложен один из вариантов повышения эффективности использования энергии топлива при работе твердотопливных котлов - путем снижения потерь тепловой энергии уменьшением температуры дымовых газов на выходе из топки за счет установки дополнительных поверхностей нагрева а именно - экономайзера. Рассмотрен алгоритм расчета водяного экономайзера для твердотопливных котлов с целью повышения его энергоэффективности. EN: In activity the algorithm for calculating the water economizer for solid fuel boilers is considered in order to increase its energy efficiency. The scheme of arrangement of low-power economizer on the basis of domestic aggregates is planned. Modern solid fuel boilers working on pellets are quite perfect. Their efficiency is 80%. The greatest loss of heat - with flue gases. They can be reduced by reducing the temperature of the flue gases after leaving the furnace, by installing additional heating surfaces. This is usually the installation - economizer. The article proposes an algorithm for calculating a water economizer with the definition of the required heat exchange surface and other parameters. Calculations are made for the boiler using as fuel - sunflower husk pellets. Equating the amount of heat given off by the combustion products to the quantity of heat perceived by water in the water economizer, we determine the enthalpy of water, after the water economizer, adopting the economizer efficiency of 0.9. The heat exchange surface area of the economizer will be found by jointly solving the heat balance and heat transfer equation. Estimated temperature in the economizer, we define as the average logarithmic. The temperature of the gases after the water economizer is limited by the danger of metal corrosion. In this regard, the flue gas temperature should be selected above the dew point temperature of flue gases by 15-20 ° C. Based on this condition and recommendations for calculating the temperature of the dew point of flue gases, the value of permissible cooling temperature of flue gases is 135 ° C. The proposed method of calculation can be used to select an economizer for a solid fuel boiler in order to increase its energy efficiency. Installing an economizer in the chimney of a solid fuel boiler increase its efficiency by 4 ... 8%. Fuel economy will be 100 ... 150 kg of pellets per boiler per day.
Повышение эффективности твердотопливных котлов
Increas the energy efficiency of solid fuel boilers
Keywords: економайзер; кількість теплоти; втрати теплоти з димовими газами; додаткові поверхні нагрівання; теплообмін; кількість труб в газоході